Aggressive Surgical Resection of Enormous Cervical Metastasis from Nasopharyngeal Carcinoma - Sha Fu; Jin-song Li; Eduardo Dias-Ribeiro; Julliana Cariry Palhano Freire; Sheng Sun; Song Fan (University of Zagreb. School of Dental Medicine, 2019)
While nasopharyngeal carcinoma (NPC) commonly presents lymphoid metastases, the enormous cervical metastasis causing dysphagia and limitation of neck motion is not a familiar symptom for most of NPC cases. We report a 23-year-old male with undifferentiated carcinoma of the nasopharynx, stage Ⅲ (T3N2M0), who had undergone aggressive surgical resection of bilateral huge cervical mass first followed by concurrent chemo-radiotherapy with cisplatin-based regimens. The postoperative clinical course was uneventful and follow-up, 2 years later, revealed no recurrence of primary lesion and neck metastases. We recommend that aggressive surgical resection may be considered when NPC patients significantly suffer clinical symptoms from a huge cervical metastasis.